Pengaruh Komitmen Organisasi terhadap Kesiapan untuk Berubah pada Dosen - Fitri Fatimah Zahra; Lisa Widawati (Bandung Conference Series: Psychology Science, 2022)
Abstract. Covid-19 pandemic has an effect on universities including the changes of academic activities, the learning system, and technology to enable the teaching staff to Work from Home. The lecturers who are actively involved in the grade achievement and the goal of the universities while the policy to Work from Home is being done show that there is an organizational commitment from the lecturers. Organizational commitment is said to have the correlation with the readiness to change so that the change that happen in the organization can achieve its success. This research aims to find and analyze the effects of Organizational Commitment on the Readiness to Change on the Lecturers of Bandung Islamic University. The research method used is causality method with the total subjects of 114 lecturers of UNISBA. This research uses the measurement tools, namely Organizational Commitment Questionnaire (OCQ) and Readiness Change Scale. Based on the results of the analysis of simple linear regression test with the significance level = 0.05, it was obtained rs = 0.523 indicating that there is a positive effect of the organizational commitment on the readiness to change on the lecturers of Bandung Islamic University. Abstrak. Pandemi COVID-19 ini berpengaruh terhadap perguruan tinggi yaitu meliputi perubahan aktivitas akademik, sistem pembelajaran, dan teknologi untuk memungkinkan staf pengajar bekerja secara Work From Home. Dosen yang terlibat aktif pada pencapaian nilai dan tujuan universitas ketika kebijakan WorkFromHome dilaksanakan, menandakan bahwa adanya komitmen organisasi pada dosen. Komitmen organisasi dikatakan berhubungan dengan kesiapan untuk berubah, sehingga perubahan yang terjadi pada organisasi dapat mencapai keberhasilannya. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh Komitmen Organisasi terhadap Kesiapan untuk Berubah pada dosen Universitas Islam Bandung. Metode penelitian yang digunakan adalah metode kausalitas dengan jumlah subjek 114 dosen UNISBA. Penelitian ini menggunakan alat ukur Organizational Commitment Questionaire (OCQ) dan Readiness Change Scale. Berdasarkan hasil uji analisis regresi linear sederhana dengan taraf signifikansi = 0.05 diperoleh rs = 0.523 yang menandakan terdapat pengaruh positif komitmen organisasi terhadap kesiapan untuk berubah pada dosen Universitas Islam Bandung sebesar 52.3%.